Spontaneous poisoning of cattle by onion (Allium cepa) in Brazil - Hugen G.F.G.P.* (2024)
© 2024 Colegio Brasileiro de Patologia Animal. All rights reserved.- Hugen G.F.G.P., Ogliari D., Wicpolt N.S., Melchioretto E., Traverso S.D., Wiser C., Hemckmeier D. & Gava A. 2024. Spontaneous poisoning by onion (Allium cepa) in cattle in Brazil. Pesquisa Veterinária Brasileira 44:e07204, 2024. Graduate Program in Animal Science, Centro de Ciências Agroveterinárias, Universidade do Estado de Santa Catarina, Av. Luiz de Camões 2090, Conta Dinheiro, Lages, SC 88520-000, Brazil. E-mail: aldo.gava@udesc.br The state of Santa Catarina is the largest national producer of onions. The consumption of onion (Allium cepa) by domestic animals can cause hemolytic anemia and hyperhemoglobinemia of Heinz bodies in erythrocytes. The epidemiological data and the pathological clinical picture were obtained during a visit to the property where the disease occurred. A herd of 54 beef cattle from a property in the municipality of Bom Retiro/SC, was placed in an onion crop, which had not been completely harvested because it was outside the desired standard for trade. The animals remained in this field for eight days. At the end of this period, all of them presented apathy, anorexia, brown urine and mucous membranes and an onion odor on expiration. The macroscopic changes observed were pale mucous membranes, blood with decreased viscosity and increased clotting time, liver with an evident lobular pattern and remains of onion in the rumen. The carcass gave off a strong onion odor. By histological analysis, there was central lobular coagulation necrosis in bridging in the liver. In the kidneys, there were intracytoplasmic hyaline droplets in tubular epithelial cells and a deposit of eosinophilic material in the lumen of the tubules. For the diagnosis of onion poisoning, epidemiological data associated with clinical signs, such as pale mucous membranes with evidence of hemoglobin pigmentation (brown mucosa) and hemoglobinuria, should be taken into account. This article seems to be the first report of onion poisoning in cattle in Brazil.